Two decades of public sector innovation: building an analytical framework from a systematic literature review of types, strategies, conditions, and results - and Criado, J. Ignacio; Alcaide-Muñoz, Laura; Liarte, Irene (Public Management Review, 2023)
Scholarly attention in innovation in the public sector is growing rapidly, provoking analytical complexity. We developed a systematic literature review about Public Sector Innovation (PSI), analysing 169 articles published between 2001 and 2021, using PRISMA. We present a comprehensive approach to PSI testing and empirically develop an analytical framework based on the most common combinations of the studied dimensions. Additionally, we propose three main research avenues for the future of PSI: (1) studying PSI in different contexts, (2) expanding the analysis of configurations in PSI initiatives, and (3) analysing ambidextrous strategies to support the practical implementation of PSI.